THE DYNAMICS OF MORPHOLOGICAL CHANGES IN THE SYNOVIAL COLLEGE OF RATS IN RATES IN EXPERIMENTAL NON-SPECIFIC ARTHRITIS AND INVEDIENCE - Pelipenko, O.V.; Shepitko, V.I.; Pelipenko, L.B. (World of Medicine and Biology, 2019)
The morphological and functional features of the synovial sheath of the knee joints of rats were studied in normal, under conditions of experimental nonspecific arthritis and with the introduction of cryopreserved placenta (CPP). The work was aimed at determining the morphological characteristics of the vascular structure of the rat’s knee joints synovial sheath in the comparative aspect in the norm, in the conditions of experimental arthritis and after exposure to cryopreserved placenta preparations. Analysis of the study data revealed a high sensitivity of the synovial tissue to the influence of exogenous factors, with different responses to homeostasis disorders. With the introduction of CPP under conditions of experimental aseptic inflammation up to 14 days, the predicted effects of collagen fibers edema were observed, much less pronounced compared to the group of animals that did not undergo the inflammatory process correction. Desquamation of the coating layer without the finding of proliferative processes was detected in separate preparations on the 3-d day of the experiment. By the 5th day, leukocyte infiltration of the vascular zones was observed, and by the 14th day, the phenomenon of venous stasis was observed. On the 21st day of the study, the morphological picture of the synovial sheath was consistent with tissue parameters in the norm. It has been established that cryopreserved placenta preparations have a positive effect on synovial tissue in inflammatory processes and can be used for prevention and treatment of nonspecific arthritis.
Keywords: synovial sheath; cryopreserved placenta; aseptic inflammation